2008
DOI: 10.1253/circj.72.926
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine Supplementation Decreases the Left Ventricular Mass in Patients Undergoing Hemodialysis

Abstract: Background Patients on long-term hemodialysis become deficient in carnitine and are frequently treated with carnitine supplementation to offset their renal anemia, lipid abnormality and cardiac dysfunction. The therapeutic value of carnitine supplementation on left ventricular hypertrophy (LVH) in patients with normal cardiac systolic function remains uncertain. Methods and ResultsThe cardiac morphology and function of 10 patients given 10 mg/kg of L-carnitine orally, immediately after hemodialysis sessions 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…It has been reported that oral L-carnitine treatment significantly improved left ventricular function [26,27], while it reduced LVMI [28]. In this study, we confirmed that L-carnitine supplementation caused a significant increase in %FS concomitantly with a reduction of BNP.…”
Section: Effects On Cardiac Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that oral L-carnitine treatment significantly improved left ventricular function [26,27], while it reduced LVMI [28]. In this study, we confirmed that L-carnitine supplementation caused a significant increase in %FS concomitantly with a reduction of BNP.…”
Section: Effects On Cardiac Parameterssupporting
confidence: 87%
“…In contrast, L-carnitine did not change LVMI. The reason for this discrepancy remains unknown, but it may be partly due to the shorter period of supplementation than in the previous study (12 months) [28].…”
Section: Effects On Cardiac Parameterscontrasting
confidence: 61%
“…Our present study suggests that patients with increased FGF-23 levels are likely to have LVH, which is the established principal risk factor driving the high rate of cardiovascular mortality in HD patients, and which may be reduced by L-carnitine supplementation. 24 In addition, we should emphasize that FGF-23 levels were associated with LVMI, irrespective of serum phosphate in our study. This finding is also consistent with the report by Gutierrez et al and Jean et al, who showed that an increased mortality in patients with elevated levels of FGF-23 was independent of serum phosphate levels.…”
Section: Association Between Fgf-23 and Lvhmentioning
confidence: 52%
“…Deficiency states, such as iron and/or erythropoietin (with attendant anemia), and perhaps carnitine deficiency as well can promote LVH (49). However, replacement of these factors have variable effects on LVH in CKD/ESRD (see below).…”
Section: What Are the Likely Pathophysiologic And Pathobiologic Mechamentioning
confidence: 99%